ENHANCING EMPLOYEE PERFORMANCE: THE TRANSFORMATIVE POWER OF GREEN HUMAN RESOURCE MANAGEMENT - Dr. Aajaz Ahmad Hajam,; Alphonsa S John (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The study aimed to investigate the impact of Green Human Resource Management on the operational effectiveness of private sector firms. A total of twenty studies were included as a sample in this inquiry. The findings of this study indicate that the implementation of Green Human Resource Management has a beneficial impact on the overall performance of a business. Enhancing organizational performance is a crucial determinant of a company's sustainability in the market. The present study's findings indicate that implementing green human resource management methods results in enhanced employee and organizational performance.